Introduction: Disruptions in global value chains – Continuity or change for labour governance? - GEREFFI, Gary; POSTHUMA, Anne Caroline; ROSSI, Arianna (International Labour Review, 2021)
Global production and trade organized in global value chains (GVCs) have structured labour governance and the conditions of work for multiple decades. Since the early 2000s, a series of new economic, technological and political disruptions, along with the current COVID‐19 global health pandemic, have accentuated critical concerns about the role of labour governance and the future of work in the global economy. The articles in this Special Issue address these themes through original industry and country case studies, using both longitudinal and comparative research designs and mixed methods to offer insights into a labour governance framework that will fit future GVCs.